Re-description of Margarinotus (Paralister) longus (Bickhardt, 1910) with a key to the species of the subgenus Paralister of the genus Margarinotus from the Balkans (Coleoptera, Histeridae, Histerinae) - Lackner, Tomáš (Zootaxa, 2016)
The holotype of Margarinotus (Paralister) longus (Bickhardt, 1910) is re-described and figured. A key to the species of the subgenus Paralister Bickhardt, 1917 of the genus Margarinotus Marseul, 1853 from the Balkans is given.